Analysis of Factors Affecting Political Participation in Rural Communities: A Case Study of Lenjan Township - Asghar Norouzi (برنامه ریزی فضایی)
AbstractParticipation is a crucial indicator of sustainable rural development and political participation serves as a benchmark for the political development of societies. In rural areas with a substantial portion of the population, fostering political engagement is essential for achieving this goal at the national level. This research evaluated and analyzed the factors influencing political participation among the villagers of Lenjan Township. The study was applied in nature, employing a descriptive-analytical and survey-based methodology. Data collection involved both library research and field methods, specifically through the administration of a researcher-designed questionnaire. A total of 250 villagers over the age of 18, eligible to participate in elections, were surveyed using a simple random sampling method and interviews. The validity of the questionnaire was confirmed by experts and its reliability was measured using Cronbach's alpha, which yielded a score of 0.78. For data analysis, appropriate descriptive statistics (mean, percentage, graphs) and inferential statistics (one-sample t-test) were applied, alongside factor analysis using SPSS, Excel, and GIS software. The results indicated that the overall level of participation was higher than average with a mean score of 3.51. Among the various components of political participation, the "voting" aspect stood out with the highest average of 4.13. Factor analysis revealed that political awareness, media influence, social factors, and government performance were the most significant determinants of political participation, collectively accounting for 65.91% of the total variance. Additionally, correlation analysis showed no significant relationship between voting participation and individual characteristics, such as gender, age, marital status, and education. Keywords: Political Participation, Election, Village, Lenjan.  IntroductionParticipation has been an integral part of human life since ancient times and its significance has only grown in contemporary society. It serves as a foundation for social solidarity and national support. As such, public participation is a fundamental condition and operational aspect of development often equated with the concept of development itself. Involvement of rural communities in shaping their own destinies is a key principle of rural governance. Political participation is essential for the political development of nations, encompassing voluntary and conscious actions taken either directly or indirectly to influence decisions related to societal administration. It plays a crucial role in assessing the legitimacy and effectiveness of political systems. Among the various forms of political participation, voting is the most practical and accessible means for citizens to engage in the political process. Numerous factors influence electoral participation and behavior, which can vary across different election cycles. Additionally, according to the latest data from the Iranian Statistics Center, 26% of the country's population resides in rural areas. Ignoring this demographic influence in elections poses significant risks to the political landscape. Therefore, this study aimed to investigate and analyze the factors affecting the level of political participation among the rural population of Lenjan Township. Materials & MethodsThis research was practical in nature, employing a descriptive-analytical and survey-based methodology. Data collection utilized both library and field methods. The library component involved reviewing books, articles, and electronic resources to compile the theoretical foundations and background relevant to the study. In the field component, the researcher visited selected villages and engaged directly with residents to administer the questionnaire. The statistical population consisted of individuals aged 18 and older. A total of 250 questionnaires were completed for analysis. The validity of the research instrument was confirmed by expert evaluation, and its reliability was established using Cronbach's alpha, yielding a score of 0.78. The study area encompassed Lenjan Township, which covered 1,171 m2 and was situated in the southwest of Isfahan Province. Research FindingsOut of the 250 respondents, 52% were men and 48% were women. The participants' ages ranged from a minimum of 18 to a maximum of 76 years, with the largest age group (29.2%) falling within the 39-48 year range. Regarding marital status, 60.8% reported being married. In terms of education, 10% of respondents were illiterate, 24.8% had completed elementary to diploma level, 27.2% held a diploma, 34% had a bachelor’s or postgraduate degree, and 4% had postgraduate qualifications beyond that. Employment status revealed that 8% of participants were unemployed, 33% were privately employed, 22% worked as government or corporate employees, 13% were students, 22% were homemakers, and 2% were identified as soldiers. Regarding household income, 21.6% reported earning below 5 million Tomans, 27.2% earned between 5 and 8 million, 22.4% earned between 9 and 12 million, 18% earned between 13 and 16 million, and 10.8% earned over 16 million Tomans. The largest household size reported was for families of 3-4 members.To evaluate the level of political participation among villagers, a one-sample t-test was conducted. In response to general questions about "political participation", the voting option had an average score of 4.13. Participation in local elections averaged 3.74, efforts to support a specific candidate averaged 3.66, affiliation with a political group averaged 3.52, and engaging in political discussions averaged 3.14. The overall average for these categories was above 3, while participation in political assemblies had the lowest average at 2.87. An analysis of the correlation between electoral participation and personal characteristics indicated no significant relationships. Specifically, the correlations were as follows: gender (0.07), age (-0.04), marital status (-0.01), and education level (0.02); none of these demonstrated a significant connection. To identify the most significant factors affecting political participation among villagers, exploratory factor analysis was employed. The results from the factor analysis conducted using SPSS software indicated that "political awareness" was the primary factor, accounting for 14.19% of the total variance. The second factor, "media", accounted for 7.47% of the variance followed by the third factor, "social factors", which accounted for 6.10%. The fourth factor, "government performance", accounted for 5.80%.Discussion of Results & ConclusionParticipation is a key indicator of sustainable rural development, with political participation serving as a crucial criterion for the political advancement of societies. In rural areas with substantial populations, fostering this participation is essential for achieving national significance. In Iran, elections are held for nearly all branches of government with a strong emphasis on increasing public participation. The current research examined and analyzed the factors influencing political participation within the rural communities of Lenjan. The findings revealed that, among the 250 respondents, 52% were male and 48% were female. The largest age group comprising 29.2% of participants fell within the 39-48 year range. Additionally, 60.8% of respondents reported being married. In terms of educational attainment, those with bachelor’s and postgraduate degrees constituted 34% of the sample, while 27.2% held a diploma. Regarding employment status, 8% were unemployed, while 55% were employed in private, government, or corporate sectors. The remaining respondents were identified as students, homemakers, or soldiers. The highest monthly household income bracket was reported by 27.2% of participants, who earned between 5 and 8 million Tomans. The results indicated that the overall level of political participation was above average with a mean score of 3.51. Among the various components of political participation, the "voting" aspect received the highest average score of 4.13. An examination of the correlation between electoral participation (voting) and individual characteristics—such as gender, age, marital status, and education—showed no significant relationships among these variables. The factor analysis results identified political awareness, media influence, social factors, and government performance as the most significant determinants of political participation in that order. In total, these 13 components accounted for 65.91% of the total variance.